ASUHAN KEPERAWATAN JIWA Nn.N DENGAN BIPOLAR AFFECTIVE DISORDER YANG BERFOKUS PADA MASALAH PERILAKU KEKERASAN DI RS X - Anggraeni Nababan, Devi; Pasaribu, Jesika (Journal Healthcare Education, 2024)
Bipolar is a mental disorder with two contradictory moods, namely depression and manic. Patients with bipolar disorder during the manic phase are often associated with increased violent behavior, because during the manic phase the patient will experience excessive euphoria, impulsiveness, and lack of self-control, causing aggressive behavior. Patients who lose control of themselves will be controlled by their anger so that the patient can harm themselves, other people and the environment, such as killing other people or themselves. The purpose of this case study is to determine the success of providing strategies for implementing violent behavior. The method used is a case study carried out by nursing care including assessment, data analysis, nursing diagnosis, planning interventions, implementation, evaluation and observation. Case studies are carried out during 1 to 4 days of monitoring. The intervention provided in this case study used direct demonstration. The results of the intervention given to patients were a reduction in signs of violent behavior in patients.